Religious traditions of the world: a journey through Africa, Mesoamerica, North America, Judaism, Christianity, Islam, Hinduism, Buddhism, China, and Japan - RELIGIOUS... (Harper Collins Publishers, 1993)
ir,c.1-4/stoc3=c.1-4